Penerapan Metode Storytelling untuk Meningkatkan Keterampilan Menyimak Cerita Rakyat Siswa Kelas V UPT SDN 8 Sangalla Selatan Kabupaten Tana Toraja - Dolla, Sepnita; Usman, Usman; Hasriani, Hasriani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to improve the listening skills of fifth-grade students at SDN 8 Sangalla Selatan, Tana Toraja Regency, through the application of the storytelling method. Problems encountered in the learning process were low student attention and active participation during listening activities, which resulted in low learning effectiveness. This study was a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection to continuously improve learning. Data were obtained through listening tests at the end of each cycle to measure student development and assess the effectiveness of storytelling. The results showed a significant improvement in listening skills. In the first cycle, only 8 out of 22 students (36.4%) achieved the Minimum Completion Criteria (KKM) with an average score of 54.09. After improvements in the second cycle, the number of students who completed the reading increased to 16 (72.7%) with an average score of 73.64. Thus, the application of the storytelling method has proven effective in improving listening skills for folktales and strengthening the quality of Indonesian language learning in elementary schools.